A strength developing model of concrete under sustained loads. (15th February 2016) - Han, Bing; Liu, Ming-Hui; Xie, Hui-Bing; Liu, Yu-Ping
Highlights: Maximum past thickness in concrete was modified considering the effect of sustained load. Strength developing rules of concrete under sustained load were explored based on compressible packing model. Experiments were executed as a case study to suggest an available process to determine the parameters in the model. Abstract: The strength of concrete will be developed as the age increases. When a sustained load is applied on the concrete, the development rules will be changed. Research on these rules is needed to estimate more rationally the developing strength of concrete used in structures than those without considering the action of sustained loads. In this paper, the development rule of compressive strength of concrete under sustained loads is explored. According to the mechanism assumption, a new model based on the Compressible Packing Model (CPM) for concrete compressive strength is proposed. For calibrating the model, experiments are carried out. Compressive strength of concrete were determined at four different ages and were compared with those of specimens without any sustained loads applied. Comparison of the results by the model and by the experiments show the model presented in this paper can be suit for concrete strength development of concrete under sustained loading.